Phenetic analysis of the genera medicagoid Trigonella, Medicago and Melilotus (Fabaceae) on seed coat in Iran - SIMA KHANDANI; MOSTAFA ASSADI; TAHER NEJADSATARI; IRAJ MEHREGAN (Biodiversitas Journal of Biological Diversity, 2016)
Khandani S, Assadi M, Nejadsatari T, Mehregan I. 2016. Phenetic analysis of the genera medicagoid Trigonella, Medicago and Melilotus (Fabaceae) on seed coat in Iran. Biodiversitas 17: 162-171. Seed morphological characters of 11 species belonging to the Medicagoid Trigonella group from Iran were studied and compared with six species of Trigonella L. (non medicagoid), one species Medicago L. and Melilotus Mill. (Fabaceae), including general shape, size, color, surface shape and testa ornamentation patterns with Scanning Electron Microscope and Stereomicroscope. Phenetic relationships among the species were studied via important seed morphological data by PCA analysis and UPMGA method. Cluster analysis of seed morphology results showed that some of medicagoid Trigonella species clustered with non medicagoid species but majority of them joined together which is in agreement of some references. In conclusion, seed morphological characters show that most Iranian medicagoid Trigonella species are well separated from the other Trigonella species. Also, some of these characters are important in systematic discriminations of the taxa.